Pengaruh Pengadukan Pada Degradasi Methylene Blue Menggunakan Katalis ZnO Terdoping Cu - Nafika Nurullita; Rahadian Zainul (Jurnal Periodic Jurusan Kimia UNP, 2022)
Methylene blue is one of the heterocyclic synthetic dyes used intextile industry, but has a negative impact on water quality and the surrounding environment. This study aims to degrade methylene blue using the photocatalytic method. The catalyst used for degradation is nano ZnO doped Cu 10%. In this study, the degradation process applies sunlight using a hexagonal mobile reactor and The light intesity is a measured using a lightmeter. The degradation process was carried out with variation of stirring at 1500 rpm and without stirring at 1,2,3, and 4 hours. The degradastion results were measured using UV-Vis spectrophotometry to see adsorption before and after degradation. Results of this study obtained the degradation using stirring has a highter percentage of degradation than without stirring. The percentage maximum of degradation obtained in study was  64,4% with a stirring speed of 1500 rpm for 4 hours irradiation. In this study showed the effect of stirring on methylene blue degradation using a hexagonal mobile reactor.